1994
DOI: 10.1073/pnas.91.9.3593
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant bisphosphoglycerate mutase variant with acid phosphatase homology degrades 2,3-diphosphoglycerate.

Abstract: To date no definite and undisputed treatment has been found for sickle cell anemia, which is characterized by polymerization of a deoxygenated hemoglobin mutant (HbS) giving rise to deformed erythrocytes and vasoocclusive complications. Since the erythrocyte glycerate 2,3-bisphosphate (2,3-DPG) has been shown to facilitate this polymerization, one therapeutic approach would be to decrease the intraerythrocytic level of 2,3-DPG by increasing the phosphatase activity of the bisphosphoglycerate mutase (BPGM; 3-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Analysis of the catalytic properties of variants have shown that Arg 89 is specifically involved in the monophosphoglycerate-binding sites (24) as has been reported for a natural human BPGM variant (25)(26)(27). In contrast, we have shown that Gly 13 is specifically involved in the diphosphoglycerate-binding sites and that replacement of Gly 13 by a positively charged amino acid residue greatly activates the phosphatase reaction, whereas the synthase and mutase reactions are greatly reduced (28).…”
mentioning
confidence: 79%
“…Analysis of the catalytic properties of variants have shown that Arg 89 is specifically involved in the monophosphoglycerate-binding sites (24) as has been reported for a natural human BPGM variant (25)(26)(27). In contrast, we have shown that Gly 13 is specifically involved in the diphosphoglycerate-binding sites and that replacement of Gly 13 by a positively charged amino acid residue greatly activates the phosphatase reaction, whereas the synthase and mutase reactions are greatly reduced (28).…”
mentioning
confidence: 79%
“…Increased levels of 2,3‐BPG are present in patients suffering from hypoxemia and anemia, because this facilitates the oxygen release of oxyhemoglobin into tissue 6. In contrast, high 2,3‐BPG levels in individuals with sickle cell anemia are harmful, because 2,3‐BPG favors sickling by facilitating the polymerization of sickle hemoglobin 79. Controlling the physiological concentration of 2,3‐BPG could yield a treatment for these diseases.…”
Section: Methodsmentioning
confidence: 99%
“…A mutation of Gly-14 of hBPGM to Ser did not modify the synthase activity, whereas the mutase and phosphatase activities were 2-fold increased or decreased, respectively. However, replacing Gly-14 with Arg enhanced phosphatase activity by 28.6-fold, whereas synthase and mutase activities were decreased 10-fold (30). In dPGMs, the equivalent residue Ser interacts with the , and marked in green background.…”
Section: Comparison With Dpgmsmentioning
confidence: 99%